Multimorbidity in adult asylum seekers: a first overview. - Carmen A Pfortmueller; Manuela Stotz; Gregor Lindner; Thomas Müller; Nicolas Rodondi; Aristomenis K Exadaktylos (PLoS ONE, 2013)
PRINCIPALS: Over the last two decades, the total annual number of applications for asylum in the countries of the European Union has increased from 15,000 to more than 300,000 people. The aim of this study was to give a first overview on multimorbidity of adult asylum seekers. METHODS: Our retrospective Swiss single center data analysis examined multimorbidity of adult asylums seekers admitted to our ED between 1 January 2000 and 31 December 2012. RESULTS: A total of 3170 patients were eligible for the study; they were predominantly male (2392 male, 75.5% versus 778 female, 24.5). The median age of the patients was 28 years (range 28-82). The most common region of origin was Africa (1544, 48.7%), followed by the Middle East (736, 23.6%). 2144 (67.6%) of all patients were not multimorbid. A total of 1183 (37.7%) of our patients were multimorbid. The mean Charlson comorbidity index was 0.25 (SD 1.1, range 0-12). 634 (20%) of all patients sufferem from psychiatric diseases, followed by chronic medical conditions (12.6%, 399) and infectious diseases (4.7%, 150). Overall, 11% (349) of our patients presented as a direct consequence of prior violence. Patients from Sri Lanka/India most often suffered from addictions problems (50/240, 20.8%, p<0.0001). Infectious diseases were most frequent in patients from Africa (6.6%), followed by the Balkans and Eastern Europe/Russia (each 3.8%). CONCLUSION: The health care problems of asylum seekers are manifold. More than 60% of the study population assessed in our study did not suffer from more than one disease. Nevertheless a significant percentage of asylum seekers is multimorbid and exhibits underlying psychiatric, infectious or chronic medical conditions despite their young age.